1993
DOI: 10.1111/j.2044-8309.1993.tb01000.x
|View full text |Cite
|
Sign up to set email alerts
|

Gaining turns and achieving high influence ranking in small conversational groups*

Abstract: Unacquainted subjects, in groups of four or five, viewed and then discussed a television programme on the topic of homosexuality. Afterwards, they ranked each group member in terms of how influential the member had been during the discussion. High‐ranking members, compared to low‐ranking members, had a greater proportion of aggregate speaking turns, thus replicating Brooke & Ng's (1986) finding. Aggregate turns were then divided into turns gained by interruptive or non‐interruptive means; and the two turn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…First, turns based upon interruption correlate strongly and positively with status (Brooke & Ng, 1986;Ng, Bell, & Brooke, 1993;Ng, Brooke, & Dunne, 1995)-interruption turns are a valid indicator of participation and status. Second, research demonstrates that interruptions can be encoded in proactive or reactive speech acts (Makri-Tsilipakou, 1994;Murata, 1994;Murray, 1987;Ng et al, 1995)-proactive content is a task-relevant contribution in the expectation states formulation.…”
Section: Interruptions Status Rewards and Sanctionsmentioning
confidence: 98%
“…First, turns based upon interruption correlate strongly and positively with status (Brooke & Ng, 1986;Ng, Bell, & Brooke, 1993;Ng, Brooke, & Dunne, 1995)-interruption turns are a valid indicator of participation and status. Second, research demonstrates that interruptions can be encoded in proactive or reactive speech acts (Makri-Tsilipakou, 1994;Murata, 1994;Murray, 1987;Ng et al, 1995)-proactive content is a task-relevant contribution in the expectation states formulation.…”
Section: Interruptions Status Rewards and Sanctionsmentioning
confidence: 98%
“…Although many factors may shape these interactions, an officer's words are undoubtedly critical: Through them, the officer can communicate respect and understanding of a citizen's perspective, or contempt and disregard for their voice. Furthermore, the language of those in positions of institutional power (police officers, judges, work superiors) has greater influence over the course of the interaction than the language used by those with less power (12)(13)(14)(15)(16). Measuring officer language thus provides a quantitative lens on one key aspect of the quality or tone of police-community interactions, and offers new opportunities for advancing police training.…”
mentioning
confidence: 99%
“…More importantly, prior research has shown that question asking and leadership emergence are related. In a study on team meeting behaviour, perceived informal leadership was related to asking for clarifications (Weaver, Pifer, & Colbeck, 2009; see also Guastello & Guastello, 1998;Ng, Bell, & Brooke, 1993; for similar findings).…”
Section: Micro-level Leadership Behaviours Representing Inquiring Andmentioning
confidence: 78%